Pengaruh Perebusan Terhadap Kadar Senyawa Fenolat Total dan Daya Antioksidan Dari Daun Kol (Brassica oleracea L. Var. capitata L.) - Mardius Syarif; Mutiara Vani; Mahyuddin Mahyuddin (Jurnal Farmasi Higea, 2009)
A determination of total phenolic compounds and antioxidant activity from cabbage leaves (Brassica olerace L var capitata L,) using spectrophotometry has been done. The determinan of total phenolic compounds was carried out according to Folin-Ciocalteu method and antioxidant activity was evaluated by DPPH method. Result of total phenolic compounds determinant showed that a fresh sample, sample boiled for 10 minutes, sample boiled for 20 minutes, sample boiled for 30 minutes were 363.395 μg/g, 44.198 μg/g, 39.510 μg/g, 33.156 μg/g while antioxidant activity at fresh sample were 60.55% in 0,1 g/mL fresh extract and for 10 minutes, sample boiled for 20 minutes, sample boiled for 30 minutes were 75.16%; 45.65%; 44.40%. Based on result of this research, concluded that treatment of boiling can reduce total phenolic compounds and antioxidant activity from cabbage leaves (Brassica olerace L. var capitata L,).